Dawr al-Mu’assasat al-Tarbawīyah al-Islāmīyah al-Taqlīdīyah fī Ta‘mīm al-Ta‘līm al-Asāsī fī Indūnīsīyā - Dhofier, Zamakhsyari (Center for Study of Islam and Society (PPIM) Syarif Hidayatullah State Islamic University, 1994)
Pesantren are Islamic educational institution unique to Indonesia. After developing into a modern Islamic educational institutions, now boarding summarizes Islamic education: education using Western methods and the national education system. Prior to 1989, there is a duality in the national education system. Public education institutions are adopting modern Western education in the field of science and technology under the Ministry of Education and Culture (Department of Education), while religious institutions, including boarding schools, under the Ministry of Religious Affairs (MORA). But once it has started early steps are required to compromise the two patterns of educational institutions.DOI: 10.15408/sdi.v1i2.857